A Holistic Community Empowerment to Increase the Youth Generation Resilience of the Social Conflict Potential in Todokuiha Village, North Halmahera Regency - Eppi Manik; Pantjar Simatupang (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
More than 20 years after horizontal conflict in Maluku, including in North Halmahera regency, the potential of the social conflict between communities is still high in the smaller scale. As a respond to this condition, the community empowerment, especially for the young generation in Todokuiha village, is carried out by stakeholders through the Hibualamo local culture approach and family economy. Through the assistance of Wahana Visi Indonesia since 2006, the community of Todokuiha have implemented Hibualamo harmony education through the Children's Forum and the Savings and Loans Association for Children's Needs (SLACN). The purpose of this study is to describe how the holistic role of community empowerment is carried out in Todokuiha as an effort to increase the resilience of the young generation from the social conflict potential. The research was carried out in September-October 2022. The data collection was carried out through observation, in-depth interviews with purposive sampling and literature study. The data analysis is mostly carried out in a qualitative descriptive manner to describe how the Children's Forum and SLACN played an important role for the development of children's education in Todokuiha village. The results showed that as many as 85% of the Children's Forum members stated that they get very good benefits of the forum for their character development. Meanwhile, 90% of the SLACN members stated that the association really helped them in supporting the family economy and children's education.